Efektivitas Ekstrak Daun Kelor (Moringa oleifera) Terhadap Kadar Trigliserida dan Glukosa Darah Sewaktu pada Tikus Jantan Galur Sprague Dawley Diabetes Melitus - Muniroh, Muniroh; Masnunah, Masnunah; Ariany, Devy (Journal of Islamic Medicine, 2024)
Background: According to data from the International Diabetes Federation (IDF), Indonesia ranks 5th in the world for the highest number of diabetes mellitus cases, with numbers predicted to continue rising. Dyslipidemia is one of the complications of diabetes mellitus, potentially leading to coronary heart disease. Kelor leaves (Moringa oleifera) contain flavonoids, which may reduce blood glucose and triglyceride levels. Objective: This study aims to evaluate the effect of Moringa oleifera leaf extract on blood glucose and triglyceride levels in male Sprague dawley rats. Methods: This experimental study involved 24 male Sprague dawley rats. Blood glucose and triglyceride levels were measured before and after administering Moringa oleifera leaf extract. The Shapiro-Wilk test assessed data normality, followed by paired t-tests, One-way ANOVA, and Pearson correlation. Results: Moringa oleifera leaf extract at a 400 mg/kg BW dose significantly reduced blood glucose levels (p=0.017). No statistically triglyceride levels decreased in all groups (p=0.195). Conclusion: Moringa oleifera leaf extract can significantly lower blood glucose levels at a dose of 400 mg/kg BW. Further research is needed to investigate the effects of Moringa oleifera on triglyceride levels